The Implementation of Convolutional Neural Network in Recognize Lontara Text - Arthanugraha, Wahyu; Zainuddin, Zahir; Arda, Abdul Latief (Universitas Bina Sarana Informatika, 2024)
The introduction of the Lontara text that is applied is still conventional in that it comes from books or teaching materials and there is no application for a translator of the Lontara text, making it difficult for students, especially those from outside the Bugis tribe. This research aims to measure the ability and apply the CNN method in the context of introducing the Lontara text. The input that use in this research is words taken from the original text or writing manuscripts of the ancient literature of the Bugis tribe